2021
DOI: 10.1002/acr2.11355
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Adoption of Telemedicine in Rheumatology Care During the COVID‐19 Pandemic Highlights Training and Supervision Concerns Among Rheumatology Trainees

Abstract: Objective To evaluate the impact of telemedicine use during the coronavirus disease 2019 (COVID‐19) pandemic on rheumatology trainees. Methods A voluntary, anonymous, web‐based survey was administered in English, Spanish, or French from August 19 to October 5, 2020. Adult and pediatric rheumatology trainees were invited to participate via social media and email. Using multiple‐choice questions and Likert scales, the survey assessed prior and current telemedicine use, im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 11 publications
0
23
0
Order By: Relevance
“…Because TM use is closely intertwined with physicians' knowledge in this domain, we strongly support the integration of digital competencies into medical education and offering of dedicated training courses for physicians [41][42][43]. Continuous education in this area seems to be particularly important, as telemedical options continuously increase, including not only medical apps but also completely new procedures such as patient self-sampling.…”
Section: Discussionmentioning
confidence: 73%
“…Because TM use is closely intertwined with physicians' knowledge in this domain, we strongly support the integration of digital competencies into medical education and offering of dedicated training courses for physicians [41][42][43]. Continuous education in this area seems to be particularly important, as telemedical options continuously increase, including not only medical apps but also completely new procedures such as patient self-sampling.…”
Section: Discussionmentioning
confidence: 73%
“…Conversely, these same studies have shown that online education struggles to find a balance between practical and theoretical learning; communication is often ineffective, and lessons are poorly optimized to the online environment. Furthermore, doctors in training report missing out on face-to-face interaction and networking opportunities and that some balance of online and in-person education would be optimal for future education [ 4 , 45 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is not only the way education is accessed that has been altered by COVID-19, but also the type of education needed. A recent international report highlighted new training needs in telemedicine, showing that, despite widespread uptake of telemedicine, only 39% of rheumatology trainees received telemedicine training, and many reported feeling less comfortable when evaluating new patients or making treatment changes using telemedicine [ 4 ]. If telemedicine is to be incorporated into future models of care, appropriate training in virtual clinical skills will be necessary.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations